KAJIAN KARAKTERISTIK EDIBLE FILM DARI TAPIOKA DAN GELATIN DENGAN PERLAKUAN PENAMBAHAN GLISEROL - Hendra, Atika Ariani; Utomo, Adrianus Rulianto; Setijawati, Erni (Widya Mandala Surabaya Catholic University, 2015)
The use of plastic as packaging material both primary and secondary is much encountered with the aim of protection to the packaged product. However, plastic can cause environmental pollution since waste from plastic is hard to decompose naturally. This can be minimized by making the packaging biodegradable and can be eaten. Edible film is a category of food packaging in the form of sheets that can be eaten together with the product. This study uses data analysis in the form of a mathematical model consisting of one factors, factors increase the concentration of glycerol, which consists of seven levels of treatment were 0%, 0.5%, 1%, 1.5%, 2%, 2.5% and 3%. Repetition performed a total of three times so that there are 21 experimental units. The parameters to be tested are tensile strength, elongation, moisture content, and Water Activity (Aw). The data obtained from each test will be analyzed by finding a mathematical model using regression analysis. Differences addition of glycerol added percentage shows a very close relationship to the attractiveness, percent elongation, moisture content, and Water Activity (Aw). The higher the percentage of glycerol is added, the percent elongation and the moisture content of edible film is increasing, while the tensile strength and Aw decreases. The maximum tensile force can be arrested by a film before it was torn ranged from 9.609 to 465.904 kg/cm2, change the maximum length of the edible film to cut off ranging between 8-108%. The water content of edible film ranges between 10:46 - 13.88%, Aw values ranging between 0551-0574.